Nutrition status as a criterion of donosologic diagnostics of teenagers health - Schudro S.А. (Medičnì Perspektivi)
The primary purpose – to give estimation of nutrition status indexes of teenagers and define their role in donosologichealth diagnostics. In the work it is proved that in 17,1% of girls anaemia was diagnosed, in 53,9% – latent deficit of iron. Clinically, symptoms of ascorbic acid deficiency were educed in 50,0%, and its maintenance in the blood serum was reduced in 70,0% of inspected. It is shown that anaemias and latent deficit of iron in teenagers are associated with their activity, anxiety and physical capacity; deficit of ascorbic acid with the changes of amino acid composition of blood and activity; violations of proteometabolism with general state, anxiety and physical capacity; increase of both lipids and blood glucose with their activity; violation of cellular immunity with activity and general state, and humoral immunity with the mental capacity of teenagers. It is necessary to take into account all these violations in donosologicdiagnostics of health of the rising generation.